2015
DOI: 10.1099/ijsem.0.000590
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium saopaulense sp. nov., a rapidly growing mycobacterium closely related to members of the Mycobacterium chelonae–Mycobacterium abscessus group

Abstract: Five isolates of non-pigmented, rapidly growing mycobacteria were isolated from three patients and, in an earlier study, from zebrafish. Phenotypic and molecular tests confirmed that these isolates belong to the Mycobacterium chelonae-Mycobacterium abscessus group, but they could not be confidently assigned to any known species of this group. Phenotypic analysis and biochemical tests were not helpful for distinguishing these isolates from other members of the M. chelonae-M. abscessus group. The isolates presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 29 publications
2
27
0
Order By: Relevance
“…There are more than 170 recognized Mycobacterium spp., including both infectious and noninfectious environmental species, which may be found in zebrafish systems and have the potential to cause disease in fish and/or human handlers. [25][26][27] Immunosuppressed handlers are particularly at risk. Seven different species have been reported to be pathogenic in zebrafish, including M. chelonae, M. marinum, M. haemophilum, M. abscessus, M. fortuitum and M. peregrinum and M. saopaulense.…”
Section: Choice Of Agentsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are more than 170 recognized Mycobacterium spp., including both infectious and noninfectious environmental species, which may be found in zebrafish systems and have the potential to cause disease in fish and/or human handlers. [25][26][27] Immunosuppressed handlers are particularly at risk. Seven different species have been reported to be pathogenic in zebrafish, including M. chelonae, M. marinum, M. haemophilum, M. abscessus, M. fortuitum and M. peregrinum and M. saopaulense.…”
Section: Choice Of Agentsmentioning
confidence: 99%
“…Seven different species have been reported to be pathogenic in zebrafish, including M. chelonae, M. marinum, M. haemophilum, M. abscessus, M. fortuitum and M. peregrinum and M. saopaulense. 25,26 These mycobacterial species are facultative pathogens that can both proliferate in the system biofilms and infect immunocompetent zebrafish. 25,27 Two of these, M. marinum and M. haemophilum, are slowly growing mycobacteria that cause obvious clinical disease and mortality in infected colonies.…”
Section: Choice Of Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…These rapidly growing nontuberculous mycobacteria (NTM) are opportunistic pathogens with the ability to form biofilms on the surface of DWDS (3). Furthermore, this complex has been implicated in invasive infections in immunocompromised hosts and is represented by M. chelonae , M. abscessus , M. immunogenum , M. salmoniphilum , M. franklinii , and M. saopaulense (410). Little information is available about the resilience of NTM in DWDS and the potential to cause public health problems (11, 12).…”
Section: Genome Announcementmentioning
confidence: 99%
“…ANI calculations were performed using the online calculator available from EzGenome (http://www.ezbiocloud.net/ezgenome/ani). Furthermore, a comparative analysis of the rpoB , recA , and sodA genes revealed <95.04% ± 0.05% sequence homology with representatives of the M. chelonae-M. abscessus complex (610). Genomic comparison confirmed that these isolates belong to the M. chelonae group but may constitute a different subspecies.…”
Section: Genome Announcementmentioning
confidence: 99%